CONSONANT CLUSTERS IN INDONESIAN LOANWORDS - Ekarina, Ekarina (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
This paper investigates two types of loanwords in Indonesian from a list published by NUSA in 1997 and the online version of Kamus Besar Bahasa Indonesia (KBBI, 2019):  those of Sanskrit origin, and of European origins. When languages borrow words from one another, they may employ various strategies in dealing with unfamiliar sounds and/or sound combinations. Overall, the study is conducted by means of descriptive qualitative method, having a focus on corpus research. Specifically, this research is concerned with the handling of syllable-initial consonant clusters that is not present in native Indonesian words. The two different patterns dealing with consonant clusters in loanwords are 1) The tendency for consonant cluster preservation in European loanwords; and 2) The tendency to insert a vowel sound to break up consonant clusters in Sanskrit loanwords. It happens due to the differences in the time frame and scope of Sanskrit and European language influences in Indonesia. The results show that onset consonant clusters have become a definite marker of loanwords in Indonesian